Impact of menstrual cycle or combined oral contraception on elite female cyclists' training responses through a clustering analysis of training sessions - Carlin, H.; Dupuit, M.; Storme, F.; Chassard, T.; Meignié, A.; Sachet, I.; Brunet, E.; Toussaint, J.-F.; Antero, J. (Frontiers in Sports and Active Living, 2024)
Objectives (i) To classify training sessions of elite female cyclists according to an intensity index based on a longitudinal follow-up using multiparametric data collected in situ (ii) to measure the effect of estimated menstrual cycle (MC) phases and oral contraceptive pills (OC) phases on the athletes' training responses on each type of training identified.